Distributed event-triggered scheme for discrete-time second-order multi-agent systems. Issue 1 (March 2017) - Quansheng, Liu; Min, Xu; Li, Peng
In order to achieve the consistency of multi-agent systems, each agent needs to communicate with its adjacent agents, which will consume energy of sensors embedded on the agents and occupy network bandwidth of multi-agent systems. Both resources are limited. To solve the above problem, a novel distributed event-triggered scheme of discrete-time second-order multi-agent systems are proposed in this article. The characteristics of the scheme have two aspects. Firstly, the event-triggered conditions are considered for the state and the velocity separately. Secondly, when the event is triggered on an agent, the agent only communicates with its local neighbors. Then, the agent and its local neighbors update their controls while the other agents' controllers remain unchanged. So the scheme can maximize reduction of the sensor energy consuming and communication burden in the multi-agent network. Based on the Lyapunov functional method, a sufficient condition is obtained to achieve the stability of the second-order multi-agent systems in terms of linear matrix inequality. Finally, numerical examples are presented to validate the proposed event-triggered consensus control.